Assessment of Entrepreneurial Leadership among Undergraduate Nursing Students: The Case from Thailand - Chawapon Sarnkhaowkhom; Siriporn Santre; Payao Phonsuk; Nathatsanan Wongtawee; Siriwimol Piansamer; Ajjita Laohapisitpanich; Wiyada Suriyalerd; Natthakarn Supapote; Thunyathon Kaewmuean; Napakaed Hosangon; Siriphorn Mathaworn; Parichat Phikunthong (Department of Nursing, Faculty of Medicine, Diponegoro University, 2022)
Background: Entrepreneurial leadership is the becoming concept in health, social sciences, business, management, and education that can influence and direct the performance and achievement of either staff or organizations. Unfortunately, entrepreneurial leadership has received limited attention in healthcare fields, especially nursing.Purpose: This cross-sectional study aimed to explore entrepreneurial leadership and examine its associated factors among undergraduate nursing students. Methods: A cross-sectional study was conducted among 410 nursing students who were recruited using a simple random sampling strategy. The data were collected using an online self-reporting survey and analyzed using descriptive statistics, Chi-square test, Fisher’s exact test, and multivariate logistic regression analysis.Results: This study’s results revealed that most nursing students generally have entrepreneurial leadership at a high level (Mean=4.04, SD=0.49). The factors significantly associated with entrepreneurial leadership among the undergraduate nursing students were the level of study year class and parental income (p<0.05).Conclusion: This study proposed critical factors influencing entrepreneurial leadership among nursing students and recommends that entrepreneurial characteristics and approaches be utilized to improve all educational aspects among undergraduate nursing students. Nursing students must learn, train, and practice entrepreneurial leadership for the development of professional skills, abilities and initiation of innovation.